Comparison of PWM and PCM Based Digital-Analog Converter Structures - Gökhan Koçyiğit; Uğur Çini (International Journal of Applied Methods in Electronics and Computers, 2016)
In this work performance limitations of various pulse-width modulation architectures are compared. First, classical pulse-width modulation based analog digital converter is analyzed. Then, pulse-count modulation based digital-analog converter is explored. The structures are implemented on Altera TM Stratix III FPGA. A sawtooth test signal is generated to analyze the performance of the DAC structures. Maximum effective resolution is calculated depending on the architecture selected. The paper is especially useful for the practicing engineers who deal with embedded system design and develop pulse-width modulation and pulse count modulation based digital-analog converters on microcontrollers and FPGA systems.